5 3
..... - ....... = 0
t-1 1+t
Soluções para a tarefa
Respondido por
0
5 3
------- - ------- = 0
t - 1 1 + t
m.m.c = (1+ t) (t - 1 )
5(1 + t)/ (1+t)(t - 1) - 3 ( t - 1 ) / (t - 1 ) (1 + t) = 0 eliminar o denominador
5 (1 + t) - 3( t - 1 ) = 0
5 + 5 t = -3 t + 3 = 0
2 t + 8 = 0
2 t = -8
t = -8/2
t = - 4
------- - ------- = 0
t - 1 1 + t
m.m.c = (1+ t) (t - 1 )
5(1 + t)/ (1+t)(t - 1) - 3 ( t - 1 ) / (t - 1 ) (1 + t) = 0 eliminar o denominador
5 (1 + t) - 3( t - 1 ) = 0
5 + 5 t = -3 t + 3 = 0
2 t + 8 = 0
2 t = -8
t = -8/2
t = - 4
Perguntas interessantes